(untitled) (Asian Journal of Applied Sciences, 2020)
This study was conducted in the Municipality of Savalou to assess endogenous knowledge related to the use of Euphorbia poissonii in the Mahi and Nago ethnic groups. The survey was conducted through individual interviews with 112 people. The Relative Frequency, the Use Value, Fidelity and Cultural Importance index were used to assess the importance of each use. Correspondence analysis (CA) was used to describe the relationship between the categories of use and ethnicities and between the parts used of the plant and the ethnics groups. The analysis showed that the plant, Euphorbia poissonii, falls under three levels of major medicinal use, including: medicinal use of the stem, sap and leaf, which is the most common practice of the Mahi sociocultural group (UV=1.58) like Nago (UV=1.35). It helps to effectively treat measles (FL=23.08), incurable wounds (FL=22.30) and scorpion sting (FL=22.30). Powder, infusion and decoction are the forms of preparation of the products most used by the skin. The two socio-cultural groups all hold and effectively various knowledge of the use of different derivatives of the plant. The importance and increasing use of Euphorbia poissonii puts this plant under various pressures and threats from the population and it has no conservation measures to this day. Finally, this study not only alerts but also provides a scientific basis to define strategies for the conservation and protection of this neglected species.